2004
DOI: 10.5858/2004-128-195-aoddts
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deaths During the Severe Acute Respiratory Syndrome (SARS) Epidemic in Singapore: Challenges in Determining a SARS Diagnosis

Abstract: Context.—An outbreak of severe acute respiratory syndrome (SARS), an infectious disease attributed to a novel coronavirus, occurred in Singapore during the first quarter of 2003 and led to 204 patients with diagnosed illnesses and 26 deaths by May 2, 2003. Twenty-one percent of these patients required admission to the medical intensive care unit. During this period, the Center for Forensic Medicine, Health Sciences Authority, Singapore, performed a total of 14 postmortem examinations for probable and suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(91 citation statements)
references
References 21 publications
(18 reference statements)
4
85
0
2
Order By: Relevance
“…Cellular infiltration by macrophages has been observed, as has a combination of macrophages and lymphocytes, with or without neutrophils. 6,8,1719,48,58,69 Large multinucleated cells identified as macrophages and pneumocytes by immunohistochemistry are frequently observed in the lungs of SARS patients. Bronchiolitis obliterans organizing pneumonia, 48 hemophagocytosis in the mononuclear cells residing in pulmonary tissues, 48 and apoptosis of epithelial cells, monocytes/macrophages, lymphocytes and pneumocytes 17 are also seen.…”
Section: Human Cases Of Sarsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular infiltration by macrophages has been observed, as has a combination of macrophages and lymphocytes, with or without neutrophils. 6,8,1719,48,58,69 Large multinucleated cells identified as macrophages and pneumocytes by immunohistochemistry are frequently observed in the lungs of SARS patients. Bronchiolitis obliterans organizing pneumonia, 48 hemophagocytosis in the mononuclear cells residing in pulmonary tissues, 48 and apoptosis of epithelial cells, monocytes/macrophages, lymphocytes and pneumocytes 17 are also seen.…”
Section: Human Cases Of Sarsmentioning
confidence: 99%
“…In some cases, coinfections by Aspergillus sp, Mucor sp, Pseudomonas aeruginosa, Klebsiella sp, methicillin-resistant Staphylococcus aureus , α-hemolytic Streptococcus sp, and cytomegalovirus have been reported. 6,19 In situ hybridization and immunohistochemistry studies have identified viral nucleic acid and/or antigen in epithelial cells from bronchi, bronchioles, trachea, and alveoli and in multinucleated cells and alveolar macrophages. 16,17,47,58,66,75 Investigation of the cytokine and chemokine profiles of SARS patients has suggested that severe SARS-related lung injury might be attributed to an excessive host immune response—particularly, the deregulation of proinflammatory cytokine production.…”
Section: Human Cases Of Sarsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of PE has been reported in intensive care unit patients with COVID‐19 7–13 . Previous outbreaks of SARS‐CoV‐1 and Middle Eastern respiratory syndrome have been associated with an increased risk of thrombosis 14,15 . Despite previous experience with these coronaviruses, the pathophysiologic characteristics of PE in SARS‐CoV‐2 infection are not well documented.…”
mentioning
confidence: 99%
“…SARS-CoV-1 infection has been associated with hematological abnormalities, including thrombocytosis (49%), elevated D-dimer (45.0%), thrombocytopenia (55%), and prolonged activated partial thromboplastin time (aPTT) (63%) (55,56). Chong et al also reported that 20.5% of patients infected with SARS-CoV-1 had deep vein thrombosis, and 11.4% of these patients showed clinical evidence of pulmonary embolism (57). Furthermore, in a SARS-CoV-1-infected patient, edema and fibrin thrombi were identified in the pulmonary vasculature (58).…”
Section: Thehemostatic Abnormalities and Pulmonary Microvascular Thrombosis In Covid-19mentioning
confidence: 99%